STUDENT SPEAKING ACTIONS IN UNDERSTANDING THE MEANING OF ENGLISH COMMUNICATION HOMOPONS IN THE LECTURE ROOM - Delpa, Delpa; Afrinda, Putri Dian (ppjbsip, 2022)
The meaning of homophones is a part of the vocabulary that is difficult to understand because the sound when the pronunciation is the same but the meaning is different. For example, the words to, two and too spoken by English users will sound the same. This causes missinterpretation in giving meaning. Along with that, basically advances in communication technology have made it easier for students to learn English related to the meaning of the homophone. Students can also learn this through various applications such as Facebook, Snack Video, Tik Tok as a teaching resource in exploring the meaning of homophones in English. In addition, students can also communicate in English with various countries based on this communication technology. The problem is that although advances in communication technology have provided space and opportunities for students to master English related to the meaning of homophones, there are still many students who do not understand the use of the meaning of homophones in English. The purpose of this study was to determine the extent to which students understand the meaning of the use of homophone words such as to, two and too to students in the lecture room. This research consists of three study rules. First, the rule of study uses the rules of a questionnaire to 500 students from various universities. Apart from that, the reviewer also used the rules of in-depth interview (In-Depth Interview) to 5 informants. The analysis of the study uses quantitative and qualitative rules where the reviewer will emphasize student speech and explanations supported by information from study informants. The objective of research about ability of the student university level how to read and heard the homophone word by the lecturer. From the analysis of the data, it can be concluded that the students easily understanding read the homophone and difficult the homophone, like to, two and too. The rule family institution teaching homophone English language to their children can improve about English language ability especially understanding homophone, like to, two and too. Besides that, communication technology can help the student learning English language about homophone.